A Case of Granulomatous Abscess of the Liver detected by 18F-fluorodeoxyglucose Positron Emission Tomography which is Very Difficult to Differ from Cholangiocellular Carcinoma - Okunaga, Yoshiki; Masuda, Takashi; Eguchi, Hidetoshi; Endo, Yuichi; Kai, Seiichiro; Shibata, Kohei; Uchida, Hiroki; Iwaki, Kentaro; Kitano, Seigo; Ohta, Masayuki (Nippon Shokaki Geka Gakkai zasshi, 2008)
A 53-year-old woman admitted for abnormal metabolic activity in the left lateral hepatic segment detected by 18F-fluorodeoxyglucose positron emission tomography had a history of cholecystolithiasis, choledocolithiasis, and acute pancreatitis. Abdominal enhanced computed tomography showed a ring-like enhanced tumor lesion 3cm in diameter in segment S3 of the liver, necessitating left lateral segmentectomy based on a preoperative diagnosis of cholangiocellular carcinoma. Macroscopically, the tumor, a yellowish white hard mass in the resected specimen, was considered cholangiocellular carcinoma. Postoperative pathological examination showed, however, that the lesion was not tumorous and had only fibrosis and proliferation of inflammatory cells and fibroblasts, leading to a diagnosis of granulomatous abscess. It is thus important to consider granulomatous abscess as a differential diagnosis of cholangiocellular carcinoma in a patient who has a history of biliary tract surgery.